The influence of strategic swimming pool facility placement on swimming performance - Izumi, T.; Hyodo, H.; Yoshioka, T.; Wada, T. (Journal of Physical Education and Sport, 2023)
Problem Statement: There are two methods for improving athletic performance: sports biomechanics and training environment. Although there are multifarious research reports on sports biomechanics—which allows for direct analyses for improving competitive performance—studies on quantitative assessment of training environment on competitive performance are lacking. Approach: We analyzed the association between the swimming competition scores achieved by each prefecture in four National Sports Festivals (71st to 74th) and the number of swimming pools present in each prefecture in Japan. The number of swimming pools was normalized for the population and area of the prefecture. Purpose: This study proposed to examine new parameters for improving competitive swimming performance by using statistical data in the training environment. Previous investigations have lacked this focus. Results: The strategic placement of pools per unit area influences performance in swimming competitions, although the pools are placed to reduce bias in the number of pools per unit population. In addition, the results quantitatively confirmed the common perception among long-time participants in swimming competitions that private indoor pools are instrumental for the successful performance of swimming competitions. School pools were also found to play a significant role. Conclusion: The study focused on indirectly improving athletic performance from objective data by adopting a data science approach, which has been lacking in previous investigations. Although this study only analyzed data from swimming competitions, similar analyses may be warranted for other sports competitions. The proposed method could have a significant impact on sports science from the perspective of sports policy and sports promotion.